Synthesis and Identification of Some New Derivatives of ([Benzyl Thio) Benzimidazole -N- (Methylene-5-Yl)] - 4,5- Di Substituted 1,2,4-Triazole and Evaluation of Their Activity as Antimicrobial and Anti-Inflammatory Agents - Al-Majidi, Suaad, M. H.; Ibrahim, Halah, A.R.; AL-issa, Yasser, A.H. (Iraqi Journal of Science, 2021)
New 2-Mercaptobenzimidazole derivatives were synthesized. 4,5-disubsitituted 1,2,4-Triazole compounds 1b-2c were synthesized from 2-(benzylthio) benzimidazole compound a, which was then reacted with (NaH) in dioxane at a temperature of (0-5 C°) to produce the salt of compound a. Then the salt was reacted with ethyl chloro acetate to yield Ethyl 2-(benzylthio) benzimidazole acetate compound b. Compound b was converted to triazole derivatives by two pathways. The first pathway was reacting compound b with semicarbazide, thiosemicarbazide and phenylsemicarbazide in DMSO as a solvent to gain compounds 1b-3b, which were then cyclized by refluxed with 2N (NaOH) to yield 1,2,4-triazole derivatives compounds 4b-6b. The second pathway involved the treatment of compound b with hydrazine hydrate to produce N-acetohydrazide-2-(benzyl thio) benzimidazole c. Compound c was refluxed with carbon disulfide (CS2) in KOH alcoholic solution to obtain the salt compound 1c. The salt was treated with hydrazine hydrate to yield 1,2,4-triazole derivative compound 2c. The newly synthesized compounds b-2c were identified by FTIR, 1H-NMR and 13C-NMR and their physical properties were measured. Furthermore, their anti-microbial activities were tested against two Gram-positive and two Gram-negative bacteria and against one strain of fungi. Also, some of these synthesized compounds were tested for their anti-inflammatory activities.